Advancements in Passive Wireless Sensing Systems in Monitoring Harsh Environment and Healthcare Applications - Wei Yue; Yunjian Guo; Jong‐Chul Lee; Enkhzaya Ganbold; Jia-Kang Wu; Yang Li; Cong Wang; Hyun Soo Kim; Young-Kee Shin; Jun-Ge Liang; Eun-Seong Kim; Nam-Young Kim (Nano-Micro Letters)
Highlights This review comprehensively examines recent advancements in passive wireless systems applied to industrial environments and biomedical sensing, with a particular focus on the design strategies of passive wireless systems. The design principles and operational mechanisms of passive wireless system components (sensing modules and readout modules) are systematically categorized. Based on the latest research, the review highlights the innovative applications of passive wireless concepts in industrial environments, equipment safety, as well as in vivo and surface signal detection.